Microsoft Office Access 2007 on demand - Johnson, Steve, 1961- (Que, 2006)
Microsoft Office Access 2007 For those who would rather be shown how than told how See How To Create databases more efficiently using a new results-oriented interface Use tools for building a database that makes information easier to find and use Import data from other programs, HTML, XML files, and other databases Use forms, filters, queries, and reports to capture and analyze data Discover ways to prevent data corruption and unauthorized access Share your data with others through interactive web pages Put your newly acquired skills to work using the online workshops Organize information and add impact with clip art, SmartArt diagrams, tables, and charts Use Groove and SharePoint Team Services to collaborate and share documents and information Prepare for the Microsoft Certified Application Specialist (MCAS) exam On the Web This book uses real-world examples to give you a context in which to use the task. This book also includes workshops to help you put together individual tasks into projects. The Access example files that you need for project tasks are available at www.perspection.com Author Bio Perspection has written and produced books on a variety of computer software-including Microsoft Office 2003 and XP, Microsoft Windows XP, Apple Mac OS X Panther, Adobe Photoshop CS2, Macromedia Flash 8, Macromedia Director MX, and Macromedia Fireworks-and Web publishing. In 1991, after working for Apple Computer and Microsoft, Steve Johnson founded Perspection, Incorporated Perspection is committed to providing information and training to help people use software more effectively. Perspection has written more than 80 computer books, and sold more Includes MCAS Exam Objectives! This courseware meets the objectives for the Microsoft Certified Application Specialist (MCAS). Upon completion of this courseware, you may be prepared to take the exam for MCAS qualification. To learn more about becoming a Microsoft Certified Application Specialist, visit www.microsoft.com. Category Database Covers Microsoft Office Access 2007 User Level Beginning-Intermediate 1 Getting Started with Access 2 Touring Access Databases 3 Planning and Creating a Custom Database 4 Working with Fields 5 Working with Tables 6 Locating Specific Information Using a Query 7 Simplifying Data Entry with Forms 8 Creating Reports to Convey Information 9 Improving the Appearance of Forms and Reports 10 Working on the Web 11 Importing and Exporting Information 12 Managing a Database 13 Prote ...